CRISPR‐based genome editing and expression control systems in Clostridium acetobutylicum and Clostridium beijerinckii. Issue 7 (13th June 2016) - Li, Qi; Chen, Jun; Minton, Nigel P.; Zhang, Ying; Wen, Zhiqiang; Liu, Jinle; Yang, Haifeng; Zeng, Zhe; Ren, Xiaodan; Yang, Junjie; Gu, Yang; Jiang, Weihong; et al.
Abstract: Solventogenic clostridia are important industrial microorganisms that produce various chemicals and fuels. Effective genetic tools would facilitate physiological studies aimed both at improving our understanding of metabolism and optimizing solvent productivity through metabolic engineering. Here we have developed an all‐in‐one, CRISPR‐based genome editing plasmid, pNICKclos, that can be used to achieve successive rounds of gene editing in Clostridium acetobutylicum ATCC 824 and Clostridium beijerinckii NCIMB 8052 with efficiencies varying from 6.7% to 100% and 18.8% to 100%, respectively. The plasmid specifies the requisite target‐specific guide RNA, the gene encoding the Streptococcus pyogenes Cas9 nickase and the genome editing template encompassing the gene‐specific homology arms. It can be used to create single target mutants within three days, with a further two days required for the curing of the pNICKclos plasmid ready for a second round of mutagenesis. A S. pyogenes dCas9‐mediated gene regulation control system, pdCASclos, was also developed and used in a CRISPRi strategy to successfully repress the expression of spo0A in C. acetobutylicum and C. beijerinckii . The combined application of the established high efficiency CRISPR‐Cas9 based genome editing and regulation control systems will greatly accelerate future progress in the understanding and manipulation of metabolism in solventogenic clostridia. Abstract : Effective genetic tools would facilitate physiological studies of solventogenic clostridia. In this study, the authors developed CRISPR‐based genome editing and expression control systems to achieve successive rounds of gene editing and gene regulation in Clostridium acetobutylicum ATCC 824 and Clostridium beijerinckii NCIMB 8052. The combined application of the established high efficiency CRISPR‐Cas9 based genome editing and regulation control systems will greatly accelerate future progress in the understanding and manipulation of metabolism in solventogenic clostridia.